Genome-wide association mapping of net form net blotch resistance in barley at seedling and adult plant stages - Rehman, Sajid; Al-Jaboobi, Muamar; Verma, Ramesh Pal Singh; Sanchez Garcia, Miguel; Visioni, Andrea (Frontiers in Agronomy, 2025)
Net form net blotch (NFNB) caused by Pyrenophora teres f. sp. teres (Ptt) is an emerging barley disease in several countries. It causes severe yield and quality losses due to infection of leaves, kernels, and stems. Owing to the inherent genetic diversity of Ptt, the incorporation of qualitative and quantitative resistance is important to obtain barley cultivars with durable resistance to NFNB. For this purpose, an association mapping panel named HI-AM (high-input association mapping panel) was screened for resistance to NFNB at the seedling stage with two virulent Moroccan Ptt isolates (Ptt40–3 and Ptt45-3) under controlled conditions, and at the adult plant stage at four hot spot locations in Morocco during different cropping seasons (2016–17 and 2017–18).​ Genome-wide association mapping (GWAM) was conducted using 13,182 PAV (presence or absence variations) and 6,311 single-nucleotide polymorphism (SNP) markers for mapping of seedling and adult plant resistance quantitative trait loci (QTLs). GWAM analysis revealed 19 QTLs for the seedling stage and 35 QTLs for the adult plant stage resistance. Of the 54 QTLs detected, 38 QTLs from this study overlapped with previously reported QTLs, while 16 QTLs were novel. Furthermore, two common seedling stage resistance and six common adult plant stage QTLs were detected, while only three QTLs overlapped for both growth stages. Seedling stage QTLs together explained 40% of the genetic variance for seedling resistance to Ptt isolate Ptt40-3, and 69% for isolate Ptt45-3, whereas the genetic variance of the QTLs for adult plant stage resistance ranged from 35% to 85%. This panel was previously used for other GWAM studies, including resistance to spot blotch and stripe rust of barley. By mapping of significant markers for three different diseases on the Morex genome version 3.0, we have identified 13 common QTLs associated with resistance to net blotch and spot blotch, and three QTLs associated with resistance to all three diseases. The identification and introgression of common QTLs conditioning resistance to three pathogens could help in attaining durable disease-resistance in barley in North Africa.